Heterogeneous Photo-Fenton Degradation of Dye RB5 using Fly Ash and Foundry Sand as Iron Source - Rajput, Himadri (My University, 2014)
This work evaluates the scope of alternative sources of iron i.e. Foundry Sand (FS), Fly Ash (FA) and mixture of FS and FA in heterogeneous photo-Fenton process for the degradation and decolorization of the dye Reactive Black5 (RB5). The aim was to see the best effect of alternative iron source i.e. FS and fly ash in terms of degradation and decolorization efficiency. EDS characterization of FS and FAconfirmed the presence of iron and aluminium which are required for photo-Fenton. A comparative assessment was attempted after initial optimization studies, viz., varying H2O2 concentration, pH, initial dye concentration, and iron (FS/Fly Ash/FS+Fly Ash) concentration. In case of FS as an iron source, results showed that the degradation and decolorization efficiency i.e. 90% was achieved in 70 min and 45 min respectively when the reaction parameters were H2O2= 2.2 mM, FS dose= 0.5 g, pH 3, initial dye concentration= 100 mgL-1. While having fly ash as an iron source 90% degradation within 30 min and 93% decolorization rates within 15 min were achieved under optimum conditions i.e., H2O2= 2.2 mM, Fly ash dose= 0.1 g, pH 3, initial dye concentration= 100 mgL-1. When a mixture of FS(0.1 g) and Fly Ash(0.05 g) is used as source of iron 99% degradation and decolorization of the dye was achieved under the reaction conditions where H2O2= 2.2 mM, Ash:Sand= 1:2, pH 3, initial dye concentration= 100 mgL-1. Thus, it is a viable option to use a mixture of FS and fly ash to have a better effect on degradation and decolorization taking advantage of the individual performance
MT, SEE
Keywords: Photo-Fenton; Degradation; RB5; Iron; Flyash; Foundry Sand